5/4x-4/3y=-5/6

Simple and best practice solution for 5/4x-4/3y=-5/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/4x-4/3y=-5/6 equation:


x in (-oo:+oo)

(5/4)*x-((4/3)*y) = -5/6 // + -5/6

(5/4)*x-((4/3)*y)-(-5/6) = 0

(5/4)*x+(-4/3)*y+5/6 = 0

5/4*x-4/3*y+5/6 = 0 // - 5/6-4/3*y

5/4*x = -(5/6-4/3*y) // : 5/4

x = (-(5/6-4/3*y))/5/4

x = -4/5*(5/6-4/3*y)

x = -4/5*(5/6-4/3*y)

See similar equations:

| 2/3x+3/4y=1 | | 1/2x-y=-1/1 | | 5/2x/1/3y=1 | | 5.8q-4.4-5.3q=0.5q-4.1 | | 5.9q-4.4-5.3q=0.5q-4.1 | | 40x+10=2 | | 40x+5=2 | | Y=ln(x^2-4x)+4 | | -0.4x-0.4y=0 | | 40x+6=4 | | -x(-4)-7= | | 40x+6=3 | | -x(-7)-7= | | 40x+6=2 | | 0.5x-0.3y=0.3 | | h(t)=-16y^2+55+6 | | -x(0)-7= | | 6.7x/0.4y=11 | | h(t)=-4.9t^2+3 | | 12-28=6x+2 | | 9x-5y=750 | | 3b+4(b+6)=-4 | | 2x-1.5+6=3 | | 6x-16y=3 | | 2x-1.5+6= | | 2(2x+4)=x+2 | | 2*-1.5+6= | | 3(2x+4)=4x+3 | | X=-x+10 | | 9x-40=6x-7 | | X=125+0.75(Y-100)+(200-10r)+150 | | 191-4x=41x+16 |

Equations solver categories